Preventive maintenance management and its relationship to the availability of the fleet truck 730e Komatsu-2013 - Alavedra-Flores, Carol (2016)
All production system is provided to operate under minimal of faults. Considering this, the research in the company Komatsu Machinery Peru S.A., it was an analysis of the current status of the equipment and determine the relationship between preventive maintenance management through its indicators and availability. Performed the analysis, the correlation coeffi cient is 79,1 %. This indicates that there is a regular degree of relationship between the variables availability MTBF and MTTR.